Draft Annual Plan 2006-07 Government of Goa - Planning Commission (Planning Commission, 2006)
Goa has emerged as the most progressive State in the country. It possesses the distinction of achieving high level of both economic and social development. An average GSDP growth of over 10% per annum, the highest per capita income and high level of human development indicators stand testimony for the levels of development achieved by the State. Many agencies have ranked Goa as No. 1 state in the country. The Eleventh Finance Commission had ranked Goa as the Best Placed State in the country in terms of infrastructure facilities. A study commissioned by India Today magazine had ranked Goa as No. 1 State in the country in terms of over all development.
Government of Goa, Directorate of Planning, Statistics and Evaluation